Analyzing Canadian Prime Minister Justin Trudeau’s Decision Making towards modernized Canada – Israel Free Trade Agreement (2015 – 2019) - Muhammad Ridho Alviora Jaya; Natasya Kusumawardani (AEGIS : Journal of International Relations, 2022)
In the beginning of the State of Israel establishment, western countries showed the most support towards the government in Tel Aviv, including Canada. Strong economic partnership between Canada and the State of Israel that was marked by the ratification of Canada-Israel Free Trade Agreement (CIFTA) back in January 1997 which became Canada’s first trade agreement outside the North American area. During the leadership of Canadian Conservative Party Prime Minister Stephen Harper, the agreement began the negotiation of modernization and was done in 2019 during the leadership period of Canadian Prime Minister Justin Trudeau. The second phase of negotiations that were held in 2017-2018 during the Trudeau period has included certain provisions that arguably believe to be Trudeau's personal concern. American and Canadian research mostly shows how Canadian’s leader in certain periods gave their support towards Israel to such an extent that they method of building relationship. Therefore, the goal of this paper is to investigate more about the leader's individual factors towards Jewish government. Question about what influence Canadian Prime Minister Justin Trudeau's decision making process towards continuing negotiations and the ratification of trade agreement was employed by the Juliet Kaarbo theory of Prime Minister Leadership style. The theory uses five variables to assess leaders’ behavior and personality. Result of this study concludes that there are some variables that have significant roles in explaining the decision-making process of Justin Trudeau during the second negotiations until the ratifications process.